EFEKTIFITAS PENEGAKAN HUKUM TINDAK PIDANA KORUPSI TERHADAP KORPORASI BERDASARKAN UNDANG-UNDANG NO. 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI - Sri Endah Indriawati (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
Practice bribery case concerning reclamation jakarta uncovered bays where the chairman of the Jakarta City Council Commission D associated with Mohamad Sanusi PT. Agung Podomoro, which makes ironic developer PT. Ocean estuary Wisesa subsidiary PT.AGUNG Podomoro Lan has been marketing the property, Jakarta Bay Reclamation sticking due to the discovery of the alleged bribery practices to the chairman of City Council Commission D of Jakarta, Mohamad Sanusi PT. Agung Podomoro, the bribe was suspected as the discussion of two draft Regional regulations (draft) on the North Coast Capital Reclamation. Here Giving Bribes suspected of violating Article 5 paragraph (1) letter a or Article 5, paragraph (1) or Article 13 of Law No. 31 of 1999 as amended in Act No. 20 of 2001 on the eradication of Corruption junto Article 55 paragraph (1) to 1 junto Article 64 paragraph (1) Criminal Code. This study intends to show the facts of corruption and money laundering. research methods with qualitative research approach based on secondary and primary data. The first study showed, was not done due to corruption and transparency monitoring data is not so up to do both, corruption repressive epektif not sufficient deterrent effect against perpetrators. Keywords: Law Imporcement, Effectifity, Corruption